KEKALAHAN SENO SAMODRO DALAM PILKADA KABUPATEN BOYOLALI TAHUN 2015 (Studi Kasus Desa Teter dan Desa Wates Kecamatan Simo Kabupaten Boyolali) - Reni Nuryani; Priyatno Harsasto (Journal of Politic and Government Studies, 2018)
Direct Regional Head Election is one of the goals of decentralization within the framework of regional autonomy. With the Direct Regional Head Election is expected to build and realize the accountability of local government. Election of Head of Boyolali District assumed how the candidates of Head of Region able to influence and win the heart of society hence participation of society of Boyolali Regency at election moment because beroroentasi on improving prosperity and empowerment of society of Boyolali Regency. Voting in the District Head Election Boyolali very dependent of the behavior of community voters Boyolali District. In addition to voter behavior from the community, the role of Head of Region in leading Boyolali District is also very important. Teter Village and Wates Village Simo District Boyolali District as one of the areas that vote in the District Head Election Boyolali Year 2015 is relatively small for the first candidate Head of Region is Seno Samodro.This study aims to determine the behavior of voters in the village of Teter and Wates Village in District Head Election Boyolali Year 2015 who feel dissatisfied with Seno Samodro so that voters divert his voice. In addition, this study also aims to determine the acquisition of Seno Samodro votes in the selection of incumbent leaders in the village of Teter and Wates village is relatively small. This research uses descriptive qualitative method with observation, interview and documentation technique.The results of this study indicate that there is disappointment and dissatisfaction of the people of Teter Village and Wates Village against Seno Samodro. This is because the policies promised by Seno Samodro to the people of Teter Village and Wates Village are not kept. Besides that, Seno Samodro is considered to have less responsibility to be the Head of Region well, then the weaknesses of Seno Samodro that happened in Teter Village and Wates Village are used by Agus Purmanto to create a strategy in attracting people sympathy to choose Agus Purmanto. Keywords : Election of Regional Head, Voter Behavior, Vote Acquisition